Impact of Training with Additional Respiratory Dead Space on Spirometry and Exercise Respiratory Pattern in Cyclists - Paulina Hebisz; Rafał G. Hebisz; Marek W. Zatoń (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2015)
The aim of our 10-week-long experiment was to investigate the impact of training with additional dead space (DS) on spirometry and exercise respiration. Respiratory muscle training is applied to the development exercise capacity. Twenty cyclists were assigned to two groups: the experimental (E) and the control (C). All of them carried on with their initial training programme. During endurance trainings (twice per week) group E used additional DS (1000 cm3). Immediatelly before and after the experiment each participant was submitted to a spirometry and a continuous test. The spirometry test measured peak inspiratory (PIF) and expiratory (PEF) flows, forced expiratory volume in one second (FEV1) and forced vital capacity (FVC). The continuous test measured tidal volume (TV), respiratory frequency (RF), along with inspiration and expiration times. Our experiment demonstrated TV increase and RF decrease in both groups. In addition, the TV value was significantly higher in group E than in C. The PIF value also increased significantly, PEF and FEV1 upward trend was observed in group E only. We concluded the additional respiratory DS used in the experimental group provoked an increase of airflow observed in the spirometry tests at rest and during intensive aerobic exercise.